Inhibitory Effect of Kurarinone on Growth of Human Non-small Cell Lung Cancer: An Experimental Study Both in Vitro and in Vivo Studies - Yang, Jie; Chen, Hao; Wang, Qiang; Deng, Shihao; Huang, Mi; Ma, Xinhua; Song, Ping; Du, Jingwen; Huang, Yun; Wen, Yanzhang; Ren, Yongshen; Yang, Xinzhou (Frontiers in Pharmacology, 2018)
Abstract Kurarinone, a flavonoid isolated from Sophora flavescens, has been reported to have significant antitumor activity. However, the cytotoxic activity of kurarinone against non-small cell lung cancer (NSCLC) cells is still under explored. In our study, we have evaluated the inhibitory effects of kurarinone on the growth of NSCLC both in vivo and in vitro as well as the molecular mechanisms underlying kurarinone-induced A549 cell apoptosis. The results showed that kurarinone effectively inhibited the proliferation of A549 cells with little toxic effects on normal liver cells. FASC examination and Hoechst 33258 staining assay showed that kurarinone dose-dependently provoked A549 cells apoptosis. Mechanistically, kurarinone significantly decreased in the ratio of Bcl-2/Bax, thereby causing the activation of Caspases 9 and Caspases 3, and reduced impact on expression of Grp78, which led to relieve the inhibition of Caspase 12 and Caspase 7, as well as suppressing the activity of AKT. Meanwhile, modeling results from the Surflex-Dock program suggested that residue Ser473 of Akt is a potential binding site for kurarinone. In vivo study, kurarinone inhibited the growth of A549 xenograft mouse models without apparent signs of toxicity. Our study indicated that kurarinone has the potential of anti-NSCLC effects, implemented through activating mitochondria apoptosis signaling pathway, as well as repressing the activity of endoplasmic reticulum pathway and AKT in A549 cells.